Selection of suitable plant geometry and profitable seasonal intercrops for henna based cropping system in arid region - Sharma, N.K. (Indian Journal of Agroforestry, 2020)
Henna (Lawsinia intermis L., family Lythraceae) is a woody perennial crop commercially cultivated for leaf production. An experiment was conducted to find out suitable plant geometry for henna cultivation and selection of companion and profitable seasonal crops for henna based cropping system. Intercropping of henna with seasonal crops is more remunerative than sole cultivation of henna. Under rainfed condition, cultivation of moong as intercrops henna at 30 cm × 250 cm plant geometry provided maximum gross return of Rs. 44955 per hectare followed by cowpea Rs. 38791/ha however; sole cultivation of henna at 50 cm × 50 cm spacing provided only Rs. 17213 per hectare. Under irrigated conditions, maximum gross return were received from a crop sequence of moong-barley (Rs. 75155/ha) which was followed by moong-isabgol (Rs.73555/ha) and moong asiliya (Rs. 72957/ha), respectively at 30 cm × 250 cm plant geometry however; intercropping of barley, isabgol and asaliya at 50 cm × 50 cm plant geometry provided Rs. 35137., Rs. 24898 and Rs. 24300/ha, respectively.